The Enhancement of Work Motivation in Agrarian Affair Office of Makassar City, South Sulawesi, Indonesia - Aslinda Aslinda; Muhammad Guntur; Henni Zainal; Andi Cudai Nur; Syurwana Farwita (Iapa Proceedings Conference, 2019)
The employees’ motivation is considered low because employees do not comply with applicable regulations. Even though in terms of income and benefits provided considered quite adequate, the low level of motivation of course will affect the work results of employees. The purpose of this study is to provide an overview of increased work motivation at the Agrarian Affair Office of Makassar city. This research is quantitative research with explanatory objectives, namely to explain the causal relationship (influence) of variables increasing work motivation at the Agrarian Affair Office of Makassar city. To measure the variables in this study, questionnaires are used. The results showed that work motivation at the Agrarian Affair Office of Makassar city was in a fairly good category. The implications of this research are to increase work motivation at the Agrarian Affair Office of Makassar city.